Cultural consonance and arterial blood pressure in urban Brazil - Dressler, W. W.; Balieiro, M. C.; Ribeiro, R. P.; Dos Santos, J. E. (Elsevier B.V., 2005)
In previous research in Brazil, we tested the hypothesis that cultural consonance is associated with arterial blood pressure. Cultural consonance is the degree to which individuals are able to approximate in their own behaviors the prototypes for behavior encoded in shared cultural models. Individuals who had higher cultural consonance in the domains of lifestyle and social support had lower blood pressures. The aim of the current research was to replicate and extend these findings. First, a more extensive cultural domain analysis was carried out, improving the description of cultural models. Second, more sensitive measures of cultural consonance were developed. Third, data were collected in the same community studied previously. The following findings emerged: (a) cultural domain analysis (using a mix of quantitative and qualitative techniques) indicated that cultural models for these domains are widely shared within the community; (b) the associations of cultural consonance in these domains with arterial blood pressure were replicated; and, (c) the pattern of the associations differed slightly from that observed in earlier research. This pattern of associations can be understood in terms of macrosocial influences over the past ten years. The results support the importance of long-term fieldwork in anthropology. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: cultural consonance; blood pressure; cultural models; Brazil